PERAN DUKUNGAN KELUARGA, DUKUNGAN PENDIDIKAN, DAN KEPERCAYAAN DIRI TERHADAP MINAT BERWIRAUSAHA (STUDI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS BUNG HATTA) - Purbo Jadmiko; Elfitra Azliyanti; Tyara Dwi Putri (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2019)
Quantitative research design was used to analyze the effect between variables of the study. Fucos research is to identify and analyse the role of perceived educational support, perceived family support against entrepreneur intention on Faculty of Economics University of Bung Hatta fields (160 respondents with the method purposive sampling) data analysis using the method of linier regression analysis to test hypotesis. The results showed that the perceived family support and self-confidence is positive and significant effect against the entrepreneur intention, whereas the perceived educational support is not supported. The discussion and research that will come under discussion on this research.